An investigation of dynamic programming models as applied to a production-smoothing problem - Asuncion, Roberto M.
The application of dynamic programming (DP) models to a production-smoothing problem is studied. Two DP model Type I (no penalty costs) and Type II (with penalty costs) are presented under consideration of deterministic demand and wherein production capacity is constrained by the number of full-shirt and overtime production available for each period of a T-period planning horizon. It is shown that under certain production situations such models can be effectively applied. The Type I Model derives a minimum-cost production plan based on given demand forecasts. The Type II Model, however, results in a set of alternative minimum-cost production plans based on an already given plan. Furthermore, in the Type II Model, a stochastic variable ("noise") is incorporated in the inventory-holding cost function to consider expected demand fluctuations.